Effect of Pineapple Shell Extracts on Browning in Fresh Vegetable and Fruit Puree and Slices - Chockchai Theerakulkait,; Patcharin Saisung, (Agriculture and Natural Resources, 2006)
The effects of pineapple shell extract (PSE) on browning in banana, potato, mushroom and apple puree and slices compared with citric acid solution (pH 3.8) (PH) and distilled water (DW) were investigated by measuring the changes in color and browning values. The browning values of banana puree treated with PSE and PH were not significantly different. They had lower browning values than that treated with DW after storage for 1 hour (p≤0.05). The browning values of banana puree treated with PSE, PH and DW were 2.95, 3.04 and 4.27, respectively. The browning value of potato puree treated with PSE was lower than those treated with PH and DW. Mushroom and apple puree treated with PSE had higher browning values than those treated with PH and DW. On the contrary, banana slices treated with PSE had a lower browning value than those treated with PH and DW during storage for 2 hours. The browning values of banana slices treated with PSE, PH and DW were 2.00, 3.10 and 5.80, respectively (p≤0.05). Potato, mushroom and apple slices treated with PSE had browning values similar to those treated with PH and DW. Therefore, the increase in browning in banana treated with PSE seemed to be less than those of potato, mushroom and apple during storage.